Social Security and Early Retirement: The Relationship Between Workers, Firms and Governments. (5th February 2013) - Lefebvre, Mathieu
ABSTRACT In this paper we survey a number of theoretical and empirical studies in order to propose explanations to the fall of labour force participation at older age. Starting from the largely studied effect of social security schemes on labour supply, we explore the employers behaviour and the role of governments in the development of early retirement schemes. We show that early retirement is the result of a global agreement between firms and government where workers have incentives to early exit the labour market due to generous non actuarial benefits. Firms have an advantage to separate older workers because they are costly compared to young workers and governments hope that by pushing elderly into early retirement they will solve the massive unemployment problem.